SHIKSHAK - E-Mentoring Application - C.V. , Ajaykrishnan; Chandran, Akhil; M.S. , Ananthu Subramanian; S. , Mithun; T. , Anjali (International Journal of Psychosocial Rehabilitation, 2020)
This thesis aims to propose a web-based mentorship application that offers to help persons in need of help in certain areas of life. With social interactions and personal lives being hosted over the internet, a web-based application seems to be an appropriate place to create a safe space for people looking for guidance from professional mentors. This application provides a safe space by offering a direct chat user interface with an expert in the identified field of interest along with avoiding the hectic questionnaires, which are commonly found in other similar applications using text classification of entered queries to identify categories and recommend mentors. This is provided in hopes of giving a clean, easy, and more personalized user experience.